A gender-based analysis of the school library usage trends of the new entrants: a case study - Wijetunge, Pradeepa; Manatunga, P.K.S. (University of Colombo, 2015)
The prior experiences in using the library resources, services and tools by the new entrants are not considered in planning the orientation programmes. A knowledge of the extent to which they have used the school library will be advantageous in providing a more context specific training in the university library. To fill this gap in knowledge the principal researcher undertook a research in several social science faculties in two Sri Lankan universities and this paper is related to the findings of the Faculty of Law. University of Colombo. Three objectives were formulated for the study; 1) to identify the gender distribution of the new entrants to the Faculty, 2) to investigate the gender-based frequency of using the school library for their GCE/AL studies, and 3) to examine the gender-based trends of using the school library. Two hundred and fifty who entered the Faculty of Law in the academic year 2015/2016, were given a structured two-page questionnaire and the results were analysed and interpreted using SPSS (Ver. 22). Findings established that 83% are female and in the 21-22 year age group and that there is no statistically significant correlation between the gender and the frequency or trends of using the school library. However, the majority (87%) of the respondents have only borrowed books and studied in the library (72.3%) while less than half (40.7%) used magazines, used the library catalogue (48.5%) and only one fourth (25.1%) have used computers in the library. The university education places significance on scholarly journal articles in addition to books, and the university library provides a computerized catalogue to locate information; besides, the students are expected to refer a range of scholarly material to underpin their classroom learning. It is strongly recommended to provide more guidance and training for the new entrants, in using the journals and the library catalogue, especially the electronic resources and tools, so that they can excel in their studies. It is also recommended to allocate more time beyond the library tour to enhance their information seeking skills
Keywords: Undergraduates, usage of school library, new entrants